Designing a Blockchain-Based Model for Zakat Management in Malaysia - Khairil Faizal Khairi; Nur Hidayah Laili; Azuan Ahmad; Murad Ali Ahmad Al-Zaqeba (RSIS International, 2025)
Indexed Publication (Tier 2)